2009
DOI: 10.1103/physrevc.80.034604
|View full text |Cite
|
Sign up to set email alerts
|

Binary reaction decays fromMg24+C12

Abstract: Charged-particle and γ decays in 24 Mg * are investigated for excitation energies where quasimolecular resonances appear in 12 C + 12 C collisions. Various theoretical predictions for the occurrence of superdeformed and hyperdeformed bands associated with resonance structures with low spin are discussed within the measured 24 Mg * excitation energy region. The inverse kinematics reaction 24 Mg + 12 C is studied at E lab ( 24 Mg) = 130 MeV, an energy that enables the population of 24 Mg states decaying into 12 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 75 publications
(145 reference statements)
0
19
0
Order By: Relevance
“…Ternary clusterizations are also predicted theoretically, but were not found experimentally in 36 Ar so far [8,58]. On the other hand, ternary fission of 56 Ni, related to its HD shapes, was identified from out-of-plane angular correlations measured in the 32 S+ 24 Mg reaction with the Binary Reaction Spectrometer at the Vivitron Tandem facility [67].…”
Section: Alpha Clustering Deformations and α Condensates In Heavier mentioning
confidence: 82%
See 2 more Smart Citations
“…Ternary clusterizations are also predicted theoretically, but were not found experimentally in 36 Ar so far [8,58]. On the other hand, ternary fission of 56 Ni, related to its HD shapes, was identified from out-of-plane angular correlations measured in the 32 S+ 24 Mg reaction with the Binary Reaction Spectrometer at the Vivitron Tandem facility [67].…”
Section: Alpha Clustering Deformations and α Condensates In Heavier mentioning
confidence: 82%
“…Highly deformed shapes and SD rotational bands have been discovered in several light α-like nuclei, such as 36 Ar and 40 Ca by using γ-ray spectroscopy techniques [57,59]. In particular, the extremely deformed rotational SD band in 36 Ar [57] is comparable in shape to the quasimolecular bands observed in both 12 C+ 24 Mg and 16 O+ 20 Ne reactions [8,58,64].…”
Section: Alpha Clustering Deformations and α Condensates In Heavier mentioning
confidence: 90%
See 1 more Smart Citation
“…There is a renewed interest in the spectroscopy of the 16 O nucleus at high excitation energy [96,99]. Exclusive data were collected on 16 O in the inverse kinematics reaction 24 Mg+ 12 C studied at E lab ( 24 Mg) = 130 MeV with the BRS in coincidence with the Euroball IV installed at the Vivitron facility [96,99]. From the α-transfer reactions (both direct transfer and deep-inelastic orbiting collisions [123]), new information has been deduced on branching ratios of the decay of the 3 + state of 16 O at 11.085 MeV ± 3 keV.…”
Section: O Nucleusmentioning
confidence: 99%
“…The high-energy level scheme of 16 O shown in Ref. [96,99] indicated that this state does not α-decay because of its non-natural parity (in contrast to the two neighbouring 4 + states at 10.36 MeV and 11.10 MeV), but it γ decays to the 2 + state at 6.92 MeV (54.6 ± 2 %) and to the 3 − state at 6.13 MeV (45.4%). By considering all the four possible transition types of the decay of the 3 + state (i.e.…”
Section: O Nucleusmentioning
confidence: 99%